2000
DOI: 10.2105/ajph.90.8.1248
|View full text |Cite
|
Sign up to set email alerts
|

Bias in proxies' reports of disability: data from the National Health Interview Survey on disability

Abstract: Use of proxies in representative surveys on disability introduces systematic biases, affecting national disability estimates.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
21
0

Year Published

2001
2001
2019
2019

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 137 publications
(21 citation statements)
references
References 14 publications
0
21
0
Order By: Relevance
“…However, although older adults and their proxies have been shown to hold similar conceptualizations of health (Lawrence, 1995), issues of bias remain even when proxy assessments are collected because of proxy-patient dyadic disagreement. Specifically, proxies tend to overreport older adults' disability (Dorevitch et al, 1992; Epstein, Hall, Tognetti, Son, & Conant, 1989; Lum, Lin, & Kane, 2005; Magaziner, Bassett, Hebel, & Gruber-Baldini, 1996; Magaziner, Simonsick, Kashner, & Hebel, 1988; Rothman, Hedrick, Bulcroft, Hickam, & Rubenstein, 1991; Santos-Eggimann, Zobel, & Berod, 1999; Todorov & Kirchner, 2000; Weinberger et al, 1992) and depressive symptoms (Bassett, Magaziner, & Hebel, 1990; Mackenzie, Robiner, & Knopman, 1989; Magaziner, Zimmerman, Gruber-Baldini, Hebel, & Fox, 1997; Teri & Wagner, 1991). In general, large discrepancies have been observed when measuring private, typically unobservable characteristics such as depressive symptoms (Epstein et al, 1989; Hung, Pickard, Witt, & Lambert, 2007; Snow et al, 2005).…”
Section: Introductionmentioning
confidence: 99%
“…However, although older adults and their proxies have been shown to hold similar conceptualizations of health (Lawrence, 1995), issues of bias remain even when proxy assessments are collected because of proxy-patient dyadic disagreement. Specifically, proxies tend to overreport older adults' disability (Dorevitch et al, 1992; Epstein, Hall, Tognetti, Son, & Conant, 1989; Lum, Lin, & Kane, 2005; Magaziner, Bassett, Hebel, & Gruber-Baldini, 1996; Magaziner, Simonsick, Kashner, & Hebel, 1988; Rothman, Hedrick, Bulcroft, Hickam, & Rubenstein, 1991; Santos-Eggimann, Zobel, & Berod, 1999; Todorov & Kirchner, 2000; Weinberger et al, 1992) and depressive symptoms (Bassett, Magaziner, & Hebel, 1990; Mackenzie, Robiner, & Knopman, 1989; Magaziner, Zimmerman, Gruber-Baldini, Hebel, & Fox, 1997; Teri & Wagner, 1991). In general, large discrepancies have been observed when measuring private, typically unobservable characteristics such as depressive symptoms (Epstein et al, 1989; Hung, Pickard, Witt, & Lambert, 2007; Snow et al, 2005).…”
Section: Introductionmentioning
confidence: 99%
“…Additionally, data cannot be construed as a national average. Furthermore, research indicates selective bias by age in over- and underreporting disabilities for others ( 7 ). Collecting data from proxies about household members may help paint a clearer picture about the characteristics of those experiencing cognitive decline and the potential burden faced by individuals and their families.…”
Section: Discussionmentioning
confidence: 99%
“…A study conducted in the United Kingdom in 1994 and 1995, based on the National Health Interview Survey on Disability, with 145,007 participants aged 18 years or over, concluded that the evaluations made by secondary informants underestimated the frequency of disability in individuals aged from 18 to 64 years, while the inverse occurred for individuals aged 65 years onwards. 15 A study that assessed the functional capacity of 287,540 individuals aged 14 years or over, using data from PNAD 2003, found that the prevalence of limitations on activities among the elderly individuals was systematically higher when the responses were provided by secondary informants. 2 Further studies are required in order to gain a better understanding of the infl uence of secondary informants on the perceptions of elderly individuals' functional capacity, since there may be differences in the perceptions of activities that are considered relevant for health assessments by the individuals themselves and by secondary informants.…”
Section: Discussionmentioning
confidence: 99%